A new method of retrieving atmospheric refractivity structure. Issue 3 (1st February 2023) - Lewis, Ollie; Brunt, Chris; Kitchen, Malcolm
ABSTRACT: It is proposed to obtain information on atmospheric refractivity structure by measuring the angle of arrival (AoA) of radio signals routinely broadcast by commercial aircraft. The angle of arrival would be measured at hill-top sites using a simple two-element interferometer. Knowledge of the aircraft's location (information conveniently contained within the broadcasts) and the AoA will enable the bending angle of the signals to be calculated. As measurable bending will only occur at grazing incidence, sources of signals either very close to the radio horizon, or at a similar height to the interferometer, are essential. The routine navigational data broadcasts from civil aircraft represent the ideal source. In areas of high air traffic density such as the UK, \~ 10 5 - 10 6 bending angle measurements may be possible each day. Numerical weather prediction models routinely assimilate bending angles retrieved from GNSS radio occultation data, so it is anticipated that assimilation methods could be developed that are able to make good use of this new source of bending angle data. Sensitivity tests were performed to estimate the resolution of humidity retrievals assuming a target AoA accuracy of 0.01°. Simulated annealing was used to demonstrate the ability to retrieve relative humidity and mixing ratio vertical profiles using AoA measurements. It is shown that for observed AoA measurements with an accuracy of 0.01° it should be possible to retrieve relative humidity and mixing ratio vertical profiles with an accuracy of \~ 5 % and \~ 0.5 g/kg respectively. An AoA accuracy of 0.01° should be achievable using hardware costing \~ €10k, however further hardware development is still required.